The impact of donor transition on continuity of maternal and newborn health service delivery in Rwenzori sub-region of Uganda: a qualitative country case study analysis - Eric Ssegujja; Justine Namakula; Allen Kabagenyi; Carol Kyozira; Timothy Musila; Henry Zakumumpa; Freddie Ssengooba (BMC, 2023)
Abstract Background The transition of donor-supported health programmes to country ownership is gaining increasing attention due to reduced development assistance for health globally. It is further accelerated by the ineligibility of previously Low-Income Countries' elevation into Middle-income status. Despite the increased attention, little is known about the long-term impact of this transition on the continuity of maternal and child health service provision. Hence, we conducted this study to explore the impact of donor transition on the continuity of maternal and newborn health service provision at the sub-national level in Uganda between 2012 and 2021. Methods We conducted a qualitative case study of the Rwenzori sub-region in mid-western Uganda which benefited from a USAID project to reduce maternal and newborn deaths between 2012 and 2016. We purposively sampled three districts. Data were collected between January and May 2022 among subnational key informants (n = 26), national level key informants at the Ministry of Health [3], national level donor representatives [3] and subnational level donor representatives [4] giving a total of 36 respondents. Thematic analysis was deductively conducted with findings structured along the WHO's health systems building blocks (Governance, Human resources for health, Health financing, Health information systems, medical products, Vaccines and Technologies and service delivery) framework. Results Overall, continuity of maternal and newborn health service provision was to a greater extent maintained post-donor support. The process was characterised by a phased implementation approach. The embedded learning offered the opportunity to plough back lessons into intervention modification which reflected contextual adaptation. The availability of successor grants from other donors (such as Belgian ENABEL), counterpart funding from the government to bridge the gaps left behind, absorption of USAID-project salaried workforce (such as midwives) onto the public sector payroll, harmonisation of salary structures, the continued use of infrastructure (such as newborn intensive care units), and support for MCH services under PEPFAR support post-transition contributed to the maintenance of coverage. The demand creation for MCH services pre-transition ensured patient demand post-transition. Challenges to the maintenance of coverage were drug stockouts and sustainability of the private sector component among others. Conclusion A general perception of the continuity of maternal and newborn health service provision post-donor transition was observed with internal (government counterpart funding) and external enablers (successor donor funding) contributing to this performance. Opportunities for the continuity of maternal and newborn service delivery performance post-transition exist when harnessed well within the prevailing context. The ability to learn and adapt, the presence of government counterpart funding and commitment to carry on with implementation were major ingredients signalling a crucial role of government in the continuity of service provision post-transition.